The Influence of Leadership Style and Education Level on Employee Performance Controlled by Work-Life Balance: A Case of PT Celebes Railway Indonesia - Jatmiko Murdiono; Sri Indah Nikensari; Agung Wahyu Handaru; Helmi Adam (PT FORMOSA CENDEKIA GLOBAL, 2023)
Employee performance determines the performance of an organization or company. However, now it is also important to ensure a work-life balance for employees. They must also make maximum contributions to the company. This study aims to analyze and determine the influence of leadership style and education level on employee performance controlled by work-life balance in the case of PT Celebes Railway Indonesia. This study is a quantitative study and found that 1) Work-life balance and employee performance have a significant impact, 2) There are differences in employee performance based on leadership style, and 3) There are differences in employee performance. The research results show that there is. Based on education level, 4) There is no interaction between leadership style and education level in determining employee performance. This study focuses on employee performance based on leadership style and employee level while continuing to use work-life balance as a control variable for employees